Modeling and Control PV-Wind Hybrid System Based On Fuzzy Logic Control Technique - Doaa M. Atia; Faten H. Fahmy; Ninet M. Ahmed; Hassen T. Dorrah (Universitas Ahmad Dahlan, 2012)
As energy demands around the world increase, the need for a renewable energy sources that will not harm the environment is increased. The overall objective of renewable energy systems is to obtain electricity with competitive cost and even benefit with respect to other energy sources. The optimal design of renewable energy system can significantly improve the economical and technical performance of power supply. This paper presents the power management control using fuzzy logic control technique. Also, a complete mathematical modeling and MATLAB/Simulink model for the proposed the electrical part of an aquaculture system is implemented to track the system performance. The simulation results show the feasibility of control technique.